The role of community organizations in efforts to achieve peace in Yemen - Esam Alahmadi (Social Empowerment Journal, 2023)
The challenging political and economic situation in Yemen hinders the effectiveness of civil society groups. Yet, these organizations continue to actively contribute to peacebuilding despite the obstacles. They emerged in response to the collapse of state institutions due to the Houthi movement's control and the subsequent Arab coalition intervention led by Saudi Arabia. Amid this, civil society stepped in to address humanitarian needs and compensate for reduced international developmental support, focusing on emergency aid. Despite the war's impact on the country's civilian life, civil society's role remains vital in territories controlled by armed groups.       This study investigates Yemen's civil society efforts in peace establishment and war alleviation. It employs analytical methods to examine activities in education, economy, politics, security, and social harmony. The goal is to highlight their role in raising peace awareness, facilitating mediation, negotiation, and dialogue. Despite Yemen's complex circumstances, civil society strives to foster peace through multifaceted actions.